# Two dice are numbered 1,2,3,4,5,6 and 1,1,2,2,3,3 respectively. They are thrown and the sum of the numbers on them is noted. Find the probability of getting each sum from 2 to 9 separately.

Last updated date: 26th Mar 2023

•

Total views: 306.6k

•

Views today: 7.84k

Answer

Verified

306.6k+ views

HINT- In order to solve such type of question we must use formula Probability \[\left( {\text{P}} \right){\text{ = }}\dfrac{{{\text{Favourable number of cases}}}}{{{\text{Total number of cases}}}}\] , along with proper understanding of favourable cases and total cases.

Complete step-by-step answer:

Here we have one unbiased dice which is numbered from 1 to 6. While other dice are biased on which numbers are 1,1,2,2,3,3.

When we through both the dice then every number of each dice will make a pair with each number of other dice so total numbers of possible outcomes will be

(1,1) (2,1) (3,1) (4,1) (5,1) (6,1)

(1,1) (2,1) (3,1) (4,1) (5,1) (6,1)

(1,2) (2,2) (3,2) (4,2) (5,2) (6,2)

(1,2) (2,2) (3,2) (4,2) (5,2) (6,2)

(1,3) (2,3) (3,3) (4,3) (5,3) (6,3)

(1,3) (2,3) (3,3) (4,3) (5,3) (6,3)

So total Favourable outcomes =36

The probability of getting each sum from 2 to 9

(1) Sum of 2

favourable outcome for Sum of 2 will be (1,1,), (1,1).

No. of favourable outcomes = 2

total number of possible cases = 36

As we know that Probability \[\left( {\text{P}} \right){\text{ = }}\dfrac{{{\text{Favourable number of cases}}}}{{{\text{Total number of cases}}}}\]

Probability (Sum of 2)=$\dfrac{2}{{36}}{\text{ = }}\dfrac{1}{{18}}$

(2) Sum of 3

a favourable outcome for Sum of 3 will be (1,2), (1,2), (2,1). (2,1)

No. of favourable outcomes = 4

total number of possible cases = 36

As we know that Probability \[\left( {\text{P}} \right){\text{ = }}\dfrac{{{\text{Favourable number of cases}}}}{{{\text{Total number of cases}}}}\]

Probability (Sum of 3)=$\dfrac{4}{{36}}{\text{ = }}\dfrac{1}{9}$

=364=91

(3) Sum of 4

a favourable outcome for Sum of 4 will be (2,2), (2,2), (3,1). (1,3)

No. of favourable outcomes = 4

total number of possible cases = 36

As we know that Probability \[\left( {\text{P}} \right){\text{ = }}\dfrac{{{\text{Favourable number of cases}}}}{{{\text{Total number of cases}}}}\]

Probability (Sum of 4)=$\dfrac{4}{{36}}{\text{ = }}\dfrac{1}{9}$

(4) Sum of 5

favourable outcome for Sum of 5 will be (1,4), (4,1,), (2,3)., (2,3) (3,2). (3,2)

No. of favourable outcomes = 6

total number of possible cases = 36

As we know that Probability \[\left( {\text{P}} \right){\text{ = }}\dfrac{{{\text{Favourable number of cases}}}}{{{\text{Total number of cases}}}}\]

Probability (Sum of 5)=$\dfrac{6}{{36}}{\text{ = }}\dfrac{1}{6}$

(5) Sum of 6

favourable outcome for Sum of 6 will be (1,5), (1,5), (2,4)., (2,4) (3,3). (3,3)

No. of favourable outcomes = 6

total number of possible cases = 36

As we know that Probability \[\left( {\text{P}} \right){\text{ = }}\dfrac{{{\text{Favourable number of cases}}}}{{{\text{Total number of cases}}}}\]

Probability (Sum of 6)=$\dfrac{6}{{36}}{\text{ = }}\dfrac{1}{6}$

(6) Sum of 7

favourable outcome for Sum of 7 will be (1,6), (1,6), (2,5)., (2,5) (3,4). (3,4)

No. of favourable outcomes = 6

total number of possible cases = 36

As we know that Probability \[\left( {\text{P}} \right){\text{ = }}\dfrac{{{\text{Favourable number of cases}}}}{{{\text{Total number of cases}}}}\]

Probability (Sum of 7)=$\dfrac{6}{{36}}{\text{ = }}\dfrac{1}{6}$

(7) Sum of 8

favourable outcome for Sum of 8 will be (2,6), (2,6,), (3,5). (3,5)

No. of favourable outcomes = 4

total number of possible cases = 36

As we know that Probability \[\left( {\text{P}} \right){\text{ = }}\dfrac{{{\text{Favourable number of cases}}}}{{{\text{Total number of cases}}}}\]

Probability (Sum of 8)=$\dfrac{4}{{36}}{\text{ = }}\dfrac{1}{9}$

(8) Sum of 9

favourable outcome for Sum of 9 will be (6,3,), (3,6).

No. of favourable outcomes = 2

total number of possible cases = 36

As we know that Probability \[\left( {\text{P}} \right){\text{ = }}\dfrac{{{\text{Favourable number of cases}}}}{{{\text{Total number of cases}}}}\]

Probability (Sum of 9)=$\dfrac{2}{{36}}{\text{ = }}\dfrac{1}{{18}}$

NOTE- In Such Types of Question first find out the total numbers of possible outcomes then find out the number of favourable cases, then divide them using the formula which stated above, we will get the required answer.

Complete step-by-step answer:

Here we have one unbiased dice which is numbered from 1 to 6. While other dice are biased on which numbers are 1,1,2,2,3,3.

When we through both the dice then every number of each dice will make a pair with each number of other dice so total numbers of possible outcomes will be

(1,1) (2,1) (3,1) (4,1) (5,1) (6,1)

(1,1) (2,1) (3,1) (4,1) (5,1) (6,1)

(1,2) (2,2) (3,2) (4,2) (5,2) (6,2)

(1,2) (2,2) (3,2) (4,2) (5,2) (6,2)

(1,3) (2,3) (3,3) (4,3) (5,3) (6,3)

(1,3) (2,3) (3,3) (4,3) (5,3) (6,3)

So total Favourable outcomes =36

The probability of getting each sum from 2 to 9

(1) Sum of 2

favourable outcome for Sum of 2 will be (1,1,), (1,1).

No. of favourable outcomes = 2

total number of possible cases = 36

As we know that Probability \[\left( {\text{P}} \right){\text{ = }}\dfrac{{{\text{Favourable number of cases}}}}{{{\text{Total number of cases}}}}\]

Probability (Sum of 2)=$\dfrac{2}{{36}}{\text{ = }}\dfrac{1}{{18}}$

(2) Sum of 3

a favourable outcome for Sum of 3 will be (1,2), (1,2), (2,1). (2,1)

No. of favourable outcomes = 4

total number of possible cases = 36

As we know that Probability \[\left( {\text{P}} \right){\text{ = }}\dfrac{{{\text{Favourable number of cases}}}}{{{\text{Total number of cases}}}}\]

Probability (Sum of 3)=$\dfrac{4}{{36}}{\text{ = }}\dfrac{1}{9}$

=364=91

(3) Sum of 4

a favourable outcome for Sum of 4 will be (2,2), (2,2), (3,1). (1,3)

No. of favourable outcomes = 4

total number of possible cases = 36

As we know that Probability \[\left( {\text{P}} \right){\text{ = }}\dfrac{{{\text{Favourable number of cases}}}}{{{\text{Total number of cases}}}}\]

Probability (Sum of 4)=$\dfrac{4}{{36}}{\text{ = }}\dfrac{1}{9}$

(4) Sum of 5

favourable outcome for Sum of 5 will be (1,4), (4,1,), (2,3)., (2,3) (3,2). (3,2)

No. of favourable outcomes = 6

total number of possible cases = 36

As we know that Probability \[\left( {\text{P}} \right){\text{ = }}\dfrac{{{\text{Favourable number of cases}}}}{{{\text{Total number of cases}}}}\]

Probability (Sum of 5)=$\dfrac{6}{{36}}{\text{ = }}\dfrac{1}{6}$

(5) Sum of 6

favourable outcome for Sum of 6 will be (1,5), (1,5), (2,4)., (2,4) (3,3). (3,3)

No. of favourable outcomes = 6

total number of possible cases = 36

As we know that Probability \[\left( {\text{P}} \right){\text{ = }}\dfrac{{{\text{Favourable number of cases}}}}{{{\text{Total number of cases}}}}\]

Probability (Sum of 6)=$\dfrac{6}{{36}}{\text{ = }}\dfrac{1}{6}$

(6) Sum of 7

favourable outcome for Sum of 7 will be (1,6), (1,6), (2,5)., (2,5) (3,4). (3,4)

No. of favourable outcomes = 6

total number of possible cases = 36

As we know that Probability \[\left( {\text{P}} \right){\text{ = }}\dfrac{{{\text{Favourable number of cases}}}}{{{\text{Total number of cases}}}}\]

Probability (Sum of 7)=$\dfrac{6}{{36}}{\text{ = }}\dfrac{1}{6}$

(7) Sum of 8

favourable outcome for Sum of 8 will be (2,6), (2,6,), (3,5). (3,5)

No. of favourable outcomes = 4

total number of possible cases = 36

As we know that Probability \[\left( {\text{P}} \right){\text{ = }}\dfrac{{{\text{Favourable number of cases}}}}{{{\text{Total number of cases}}}}\]

Probability (Sum of 8)=$\dfrac{4}{{36}}{\text{ = }}\dfrac{1}{9}$

(8) Sum of 9

favourable outcome for Sum of 9 will be (6,3,), (3,6).

No. of favourable outcomes = 2

total number of possible cases = 36

As we know that Probability \[\left( {\text{P}} \right){\text{ = }}\dfrac{{{\text{Favourable number of cases}}}}{{{\text{Total number of cases}}}}\]

Probability (Sum of 9)=$\dfrac{2}{{36}}{\text{ = }}\dfrac{1}{{18}}$

NOTE- In Such Types of Question first find out the total numbers of possible outcomes then find out the number of favourable cases, then divide them using the formula which stated above, we will get the required answer.

Recently Updated Pages

If a spring has a period T and is cut into the n equal class 11 physics CBSE

A planet moves around the sun in nearly circular orbit class 11 physics CBSE

In any triangle AB2 BC4 CA3 and D is the midpoint of class 11 maths JEE_Main

In a Delta ABC 2asin dfracAB+C2 is equal to IIT Screening class 11 maths JEE_Main

If in aDelta ABCangle A 45circ angle C 60circ then class 11 maths JEE_Main

If in a triangle rmABC side a sqrt 3 + 1rmcm and angle class 11 maths JEE_Main

Trending doubts

Difference Between Plant Cell and Animal Cell

Write an application to the principal requesting five class 10 english CBSE

Ray optics is valid when characteristic dimensions class 12 physics CBSE

Give 10 examples for herbs , shrubs , climbers , creepers

Write a letter to the principal requesting him to grant class 10 english CBSE

List out three methods of soil conservation

Epipetalous and syngenesious stamens occur in aSolanaceae class 11 biology CBSE

Change the following sentences into negative and interrogative class 10 english CBSE

A Short Paragraph on our Country India